Reversible transition from ferrofluid drop to spikes due to an approaching magnet. (1st February 2022) - Jain, S. K.; Banerjee, U.; Mandal, C.; Sen, A. K.
Abstract: Remarkably, we experimentally evidenced normal field instability-driven reversible transition from ferrofluid droplet to spikes, when a sessile ferrofluid drop is exposed to a varying magnetic field gradient due to an approaching magnet, without flipping its direction of motion. We find the reversible transition is attributed to the critical magnetization of the ferrofluid and a characteristic wavelength that control normal-field instability. We extend the theory of magnetic instability by including non-uniformity in the magnetic field in all directions to predict the critical condition for transition, which is in good agreement with experiments. The spacing between spikes and spike height, and the number of spikes measured from experiments are in agreement with existing theory.